The Role of Multimodality Imaging After Cesarean Delivery. Issue 1 (March 2015) - Rezvani, Maryam; Shaaban, Akram M.; Kennedy, Anne M.
Abstract : Abstract: There has been a global increase in the rate of cesarean delivery during the last 30 years. As a result, many women of reproductive age now have uterine scars. Well-recognized obstetric and gynecologic consequences include cesarean scar pregnancy, scar dehiscence or rupture, and scar endometriosis. More recently, abnormal menstrual bleeding, pelvic pain, and secondary infertility have been reported as a consequence of cesarean delivery. This article reviews the range of normal imaging findings after cesarean delivery, as well as the imaging manifestations of complications, both acute and chronic.